FRI0141 The effect of patellar non-resurfacing during total knee arthroplasty in patients with rheumatoid arthritis. (23rd January 2014) - Ravlic-Gulan, J.; Novak, S.; Schnurrer Luke-Vrbanić, T.; Jurdana, H.; Šestan, B.; Gulan, G.
Abstract : Background: Anterior knee pain is the most common complication after total knee replacement and patellofemoral problems were recognized as a major cause. The question whether to resurface the patella or not during total knee replacement still remains controversial and unresolved. Most authors agree that in patients with rheumatoid arthritis (RA) patella should be resurfaced because it has been proposed that residual articular cartilage of the unresurfaced patella may continue to provide an antigenic stimulus for synovial inflammation. Objectives: The aim of the study was to examine the effect of patellar non-resurfacing on clinical and radiological outcome in RA patients that underwent total knee replacement. Methods: Patients were divided in two groups with 30 patients in each. The first group comprised patients with osteoarthritis (OA) and the second with RA. Standard medial patellofemoral approach was used in both groups. Majority of patients in OA group had varus, while in RA group had valgus knee deformity. Patella was denervated with electrocautery and shaped with rongeur regardless the shape. Patients were followed 5 years after surgery by x-ray and clinical examination using Hospital for Special Surgery Score (HSS), Knee Society Score (KSS) and Patellar (Bartlett) score. Subjective satisfaction with operation was also examined. Only knees with radiologically properly implanted femoral and tibial components were analysed. Position of the patella on x-ray skyline view was not used as excluding criteria. Results: In OA group HSS score was 81, 9 (70 – 90), the average KSS Score 82, 5 (71-95) and Patellar score 23.4 (18 – 27). In RA group: the average HSS score was 82, 3(50 – 89), average KSS was 80, 6 (58 – 89) and Patellar score 21, 7 (15 – 25). Comparison between examined groups using Mann-Whitney U-test (p > 0.05) did not show statistically significant differences. Interestingly, in spite of somewat lower scores in RA group of patients they described more satisfaction with operations. X-ray analysis of patellar position on skyline view showed that 10 (30%) patients in OA group showed some degree of hyperpression, while in the group of RA patients, 15 patients (50%) had lateral hyperpression. Conclusions: According to our results based on 5 years follow up, patella non-resurfacing in RA group of patients showed no statistical difference regarding clinical and radiological results in comparison with OA group. References: Rodriguez JA, Saddler S, Edelman S, Ranawat CS. Long-term results of total knee arthroplasty in class 3 and 4 rheumatoid arthritis. J Arthroplasty. 1996;11(2):141-5. Fern ED, Winson IG, Getty CJ. Anterior knee pain in rheumatoid patients after total knee replacement. Possible selection criteria for patellar resurfacing. J Bone Joint Surg Br. 1992;74(5):745-8. Feller JA, Bartlett RJ, Lang DM. Patellar resurfacing versus retention in total knee arthroplasty. J Bone Joint Surg Br. 1996;78(2):226-8. Beaupre L, Secretan C, Johnston D, Lavoie G.A Randomized controlled trial comparing patellar retention versus patellar resurfacing in primary total knee arthroplasty: 5–10 year follow-up. BMC Res Notes. 2012 Jun 7;5:273. Disclosure of Interest: None Declared